2019
DOI: 10.1111/nmo.13540
|View full text |Cite
|
Sign up to set email alerts
|

Acotiamide affects antral motility, but has no effect on fundic motility, gastric emptying or symptom perception in healthy participants

Abstract: Background Acotiamide, a prokinetic agent was shown to be efficacious in the treatment of functional dyspepsia (FD). The exact mechanism of action is incompletely elucidated. Methods This randomized, placebo‐controlled, cross‐over study aimed to examine the effect of acotiamide on gastric motility, measured as intragastric pressure, gastric emptying (GE) rate and gastrointestinal (GI) symptom perception in healthy volunteers (HVs). Participants were treated with acotiamide (100 mg tid) and placebo for 3 weeks,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…The finding that acotiamide had no effect on the gastric emptying rate is consistent with the results reported by Zai et al (5) and Masuy et al (7) The effects of commonly used drugs on gastric emptying in patients with functional gastrointestinal disease are summarized in Table 2. (5)(6)(7)(15)(16)(17)(18)(19)(20) In clinical settings, various drugs are used to treat dyspepsia in patients with functional gastrointestinal disease, but few drugs improve gastric emptying. Proton pump inhibitors, which are frequently used to treat dyspepsia in patients with functional gastrointestinal disease, delay gastric emptying.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The finding that acotiamide had no effect on the gastric emptying rate is consistent with the results reported by Zai et al (5) and Masuy et al (7) The effects of commonly used drugs on gastric emptying in patients with functional gastrointestinal disease are summarized in Table 2. (5)(6)(7)(15)(16)(17)(18)(19)(20) In clinical settings, various drugs are used to treat dyspepsia in patients with functional gastrointestinal disease, but few drugs improve gastric emptying. Proton pump inhibitors, which are frequently used to treat dyspepsia in patients with functional gastrointestinal disease, delay gastric emptying.…”
Section: Discussionsupporting
confidence: 89%
“…The reported effects of acotiamide on gastrointestinal function are summarized in Table 3. (5)(6)(7)(25)(26)(27) Many reports indicate that acotiamide has no effect on gastrointestinal function. Current trackable gastrointestinal function tests may not be able to detect changes in gastrointestinal function caused by acotiamide.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acotiamide [ClinicalTrials.gov: NCT03402984 (phase 2)], a muscarinic receptor antagonist (acetylcholinesterase inhibitor), antagonizes the presynaptic muscarinic receptors and has a prokinetic effect throughout the gut ( Altan et al, 2012 ; Masuy et al, 2019a ) and has been developed and approved in Japan and India for the treatment of FD. Studies have shown its efficacy in improving impaired gastric accommodation in patients with FD ( Altan et al, 2012 ; Matsueda et al, 2012 ).…”
Section: Prokinetic Agentsmentioning
confidence: 99%